Synthesis and Characterization of Super Bulky β-Diketiminato Group 1 Metal Complexes - Dafydd D. L. Jones; Samuel Watts; Cameron Jones (Inorganics, 2021)
Sterically bulky β-diketiminate (or Nacnac) ligand systems have recently shown the ability to kinetically stabilize highly reactive low-oxidation state main group complexes. Metal halide precursors to such systems can be formed via salt metathesis reactions involving alkali metal complexes of these large ligand frameworks. Herein, we report the synthesis and characterization of lithium and potassium complexes of the super bulky anionic β-diketiminate ligands, known [TCHPNacnac]− and new [TCHP/DipNacnac]− (ArNacnac = [(ArNCMe)2CH]−) (Ar = 2,4,6-tricyclohexylphenyl (TCHP) or 2,6-diisopropylphenyl (Dip)). The reaction of the proteo-ligands, ArNacnacH, with nBuLi give the lithium etherate compounds, [(TCHPNacnac)Li(OEt2)] and [(TCHP/DipNacnac)Li(OEt2)], which were isolated and characterized by multinuclear NMR spectroscopy and X-ray crystallography. The unsolvated potassium salts, [{K(TCHPNacnac)}2] and [{K(TCHP/DipNacnac)}∞], were also synthesized and characterized in solution by NMR spectroscopy. In the solid state, these highly reactive potassium complexes exhibit differing alkali metal coordination modes, depending on the ligand involved. These group 1 complexes have potential as reagents for the transfer of the bulky ligand fragments to metal halides, and for the subsequent stabilization of low-oxidation state metal complexes.